Ուսումնական դրդապատճառներ. տեսակներն ու առանձնահատկությունները - Մառլենա Ալեքյան (ՀՀ ԳԱԱ հրատ.)
Формирование побудительных причин к обучению считается одной из важнейших задач современной школы. Мотивация обучения рассматривается как показатель эффективности образовательной деятельности, приводится классификация и интерпретация указанных мотивов. Formation of motivation towards teaching is considered to be one of the most important tasks of modern school. Teaching motivation is considered to be an indicator of the effectiveness of educational activities, a classification and interpretation of these motives is being provided.
Keywords: Education; Theory and practice of education